2015
DOI: 10.1038/srep08860
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a vitamin D3 decomposition product bactericidal against Helicobacter pylori

Abstract: This study demonstrated that the vitamin D3 decomposition product VDP1 exerts an antibacterial action against Helicobacter pylori but not against other bacteria. Treatment with VDP1 induced a collapse of cell membrane structures of H. pylori and ultimately lysed the bacterial cells. A unique dimyristoyl phosphatidylethanolamine in the membrane lipid compositions contributed to the interaction of VDP1 with H. pylori cells. In separate experiments, VDP1 had no influence on the viability of the human cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 49 publications
4
56
0
1
Order By: Relevance
“…Similar trend has been reported in worldwide . In general, vitamin D is recognized as vital molecule in the homeostasis of calcium and phosphate levels; vitamin D deficiency has been implicated in the diverse pathological conditions such as hypomagnesemia , auto‐antibodies induction , and Helicobacter pylori infection .…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar trend has been reported in worldwide . In general, vitamin D is recognized as vital molecule in the homeostasis of calcium and phosphate levels; vitamin D deficiency has been implicated in the diverse pathological conditions such as hypomagnesemia , auto‐antibodies induction , and Helicobacter pylori infection .…”
Section: Introductionsupporting
confidence: 68%
“…Vitamin D deficiency was shown to be associated with increased autoimmune responses . Moreover, the induction of auto‐antibodies found in this patient could be associated with the H. pylori infection , and vitamin D deficiency could potentiate the host to H. pylori infection . Careful follow‐up is continuously required.…”
Section: Discussionmentioning
confidence: 82%
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Cytological research has also found that vitamin D 3 decomposition product 1 (VDP1) can lyse H. pylori bacterial cells by inducing the collapse of the cell membrane …”
Section: Introductionmentioning
confidence: 99%
“…One in vitro study showed the selective antibacterial effect of vitamin D3 decomposition product (VDP1) against H.pylori. 27 Vitamin D is also known to regulate the expression of antimicrobial peptides -cathelicidin and β-defensin, which kill the bacteria. Although the effect of cathelicidin has been demonstrated only in macrophages infected with M. tuberculosis, antibacterial action against gram-negative and gram-positive bacteria has also been reported.…”
Section: (Oh)d < 10ng/ml 25(oh)d ≥ 10ng/mlmentioning
confidence: 99%